2020
DOI: 10.3390/bios10120196
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Liquid Metal Nanoparticles: A Critical Review

Abstract: This review is focused on the basic properties, production, functionalization, cytotoxicity, and biomedical applications of liquid metal nanoparticles (LMNPs), with a focus on particles of the size ranging from tens to hundreds of nanometers. Applications, including cancer therapy, medical imaging, and pathogen treatment are discussed. LMNPs share similar properties to other metals, such as photothermal conversion ability and a propensity to form surface oxides. Compared to many other metals, especially mercur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 73 publications
(144 reference statements)
0
56
0
Order By: Relevance
“…[ 54 ] Compared to the conventional liquid metals (i.e., mercury), the low toxicity of gallium and gallium‐based liquid metals make them promising candidates for various biomedical applications, such as drug delivery, tumor therapy, biosensing, and neural interfaces. [ 27,55–59 ] Recent studies have shown the therapeutic effects of gallium‐based materials and their biocompatibility. Yang et al.…”
Section: Properties Of Liquid Metalsmentioning
confidence: 99%
“…[ 54 ] Compared to the conventional liquid metals (i.e., mercury), the low toxicity of gallium and gallium‐based liquid metals make them promising candidates for various biomedical applications, such as drug delivery, tumor therapy, biosensing, and neural interfaces. [ 27,55–59 ] Recent studies have shown the therapeutic effects of gallium‐based materials and their biocompatibility. Yang et al.…”
Section: Properties Of Liquid Metalsmentioning
confidence: 99%
“…For further information on the biomedical applications of Ga particles and nanoparticles, see two recent review papers. [36,37]…”
Section: Toxicitymentioning
confidence: 99%
“…Here, the properties of LMMMs related to motors will be discussed for better utilization of LM in MNMTs. More specific investigation and discussion about LMNPs such as surface microenvironment modification [ 42 ], nanocomposite [ 27 ], and biomedical [ 43 ] or chemical [ 44 ] applications can be found in recent reviews.…”
Section: Physicochemical Characteristics Of Micro/nanoscale Lmsmentioning
confidence: 99%